Limitaciones de la planificación territorial departamental, el POTD (2016)
New tools for spatial planning have emerged in Colombian since the promulgation of the Territory management Act (Ley Orgánica de Ordenamiento Territorial LOOT) in 2011: Departmental Guidelines and Departmental Land Management Plan. This paper focus on how those tackle four territorial challenges: the multiescalar levels of territory from national to local ones, market intervention and property rights, and the capacity to provide territorial support to human activities. The results show some limitations of those to contribute to the purpose of a multi-level and multiscale planning in Colombia and limitations to play the role of intermediary of national and local interests, and some of the possibilities of departmental action to account for a territorial model articulated nationally.